Kazakh Tobet dogs in the genomic landscape: refining the history of livestock guardian breeds - Anastassiya Perfilyeva; Kira Bespalova; Yelena Kuzovleva; Mamura Begmanova; Almira Amirgaliyeva; Olga Vishnyakova; Inna Nazarenko; Sergey Bespalov; Assel Zhaxylykova; Arailym Yerzhan; Kanagat Yergali; Yuliya Perfilyeva; et al. (BMC Biology)
Abstract Background Despite the growing body of research on livestock guarding dog (LGD) breeds, Central Asian LGDs remain significantly underrepresented in genetic studies. Additionally, while some research has explored the genetic basis of selective traits in LGDs, significant gaps remain. By investigating the genetic diversity, evolutionary history, and adaptive traits of the Kazakh Tobet, a Central Asian LGD breed from Kazakhstan, we aim to contribute to a deeper understanding of the genetic basis that characterizes LGD breeds. Results We analyzed the genetic relatedness of Kazakh Tobet dogs by combining SNP data from 90 unrelated Kazakh Tobets with publicly available SNP data from 124 dogs from 17 LGD breeds, 1753 dogs from 140 non-LGD breeds, 551 free-ranging dogs, and 16 wolves. The Kazakh Tobets exhibit considerable genetic diversity. Phylogenetic and PCA analyses suggest a common genetic origin with LGDs from Central and West Asia, which was complicated by gene flow from European LGDs. Signs of introgression from East Asian and Arctic non-LGDs may indicate a historical or modern gene exchange affecting the Kazakh Tobet lineage. Genetic clustering with free-ranging dogs supports the idea that open breeding systems do not compromise the functional integrity of LGD traits. Selection scans identified eight genomic regions with 127 genes associated with cognitive function, immune response, and metabolic regulation, suggesting the evolutionary importance of these traits in Kazakh Tobets. Conclusions This study provides new insights into the genetic history of LGD breeds and their connections to the broader genetic landscape of non-LGD breeds.